Optimization of free radical scavenging capacity and pH of Hylocereus polyrhizus peel by Response Surface Methodology. (March 2018) - Putranto, A W; Dewi, S R; Puspitasari, Y; Nuriah, F A
Abstract: Red dragon fruit ( Hylocereus polyrhizus ) peel, a by-product of juice processing, contains a high antioxidant that can be used for nutraceuticals. Hence, it is important to extract and investigate its antioxidant stability. The aim of this study was to optimize the free radical scavenging capacity and pH of H. polyrhizus peel extract using Central Composite Design (CCD) under Response Surface Methodology (RSM). The extraction of H. polyrhizus peel was done by using green-Pulsed Electric Field (PEF)-assisted extraction method. Factors optimized were electric field strength (kV/cm) and extraction time (seconds). The result showed that the correlation between responses (free radical-scavenging capacity and pH) and two factors was quadratic model. The optimum conditions was obtained at the electric field strength of 3.96 kV/cm, and treatment time of 31.9 seconds. Under these conditions, the actual free radical-scavenging capacity and pH were 75.86 ± 0.2 % and 4.8, respectively. The verification model showed that the actual values are in accordance with the predicted values, and have error rate values of free radical-scavenging capacity and pH responses were 0.1% and 3.98%, respectively. We suggest to extract the H. polyrhizus peel using a green and non-thermal extraction technology, PEF-assisted extraction, for research, food applications and nutraceuticals industry.